Estimadores de regresión logística para tratamiento de no respuesta en el caso de cocientes de variables dicotómicas (2009)
To make the estimate of ratio with dichotomic variables in a SISI design is used auxiliary information for the second stage elements. Auxiliary information is used in the numerator and denominator with the use of logistic regression. To different link functions in the logistic regression model and the treatment of the nonresponse, it is compared the eﬃciency of the use of diﬀerent types of binary auxiliary information for numerator and denominator. Through of a Monte Carlo Simulation process is made the comparison of the diﬀerent approaches.